Para-Romani in Scandinavia - Hancock, Ian (Lesya Ukrainka Volyn National University, 2021)
The study of Language Contact has come very much to the fore in sociolinguistics in recent years, and it is not surprising that Romani, a diaspora language, should receive a good share of attention. Since its very departure from India a millennium ago, its speakers have encountered and interacted with speakers of dozens of other languages, all of which have left their mark. The most extreme cases are the so-called Para-Romani varieties, which have demanded the question, are they Romani with massive non-Romani intrusion, or are they non-Romani languages with more or less Romani intrusion? This is addressed in the following article, which deals with one such para-language, called here Scandoromani. Other para-Romani languages are Angloromani, Scottish Romani, Spanish Romani (Caló), Finish Romani (Kále). Paralanguages are used for communication between members of different language and cultural communities. The paralanguages of Romani are not so well-investigated and described, and the present study brings a new light to the field of Romani linguistics. Para-Romani languages are divided into two big groups: based on Indo-European and based on non-Indo-European languages. In this case the Scandoromani is based on Indo-European languages and the Crimean-Romani (in Ukraine based on Crimean Tatar) and Kurbetcha (in Cyprus based on Turkish) are based on non-Indo-European languages. The Para-Romani varieties in Europe are preserved through communication between elder generations and children and thousands of children around Europe learn their mother tongue – the variety of Para-Romani through the transmission form parents to children. This gives the hope that those varieties will not despair.
Keywords: Romani; language contact; Scandinavia; identity; cryptolect